2007
DOI: 10.1093/jaoac/90.5.1219
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Chromatographic Determination of 6-, 8-, 10-Gingerol, and 6-Shogaol in Ginger (Zingiber officinale) as the Raw Herb and Dried Aqueous Extract

Abstract: The determination of 6-, 8-, 10-gingerol, and 6-shogaol in dried ginger (Zingiber officinale) and in the dried aqueous extract of ginger is reported. This is the first study to report a validated method for the determination of these 4 analytes. Several extraction solvents and methods were examined, and the optimum combination was determined. The samples were extracted at room temperature by sonication with methanol, and the extract was analyzed by liquid chromatography with photodiode array detection. A C18 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 0 publications
2
30
0
10
Order By: Relevance
“…Honokiol is a phenylpropanoid molecule isolated and identified in several species belonging to the genus Magnolia (such as Magnolia officinalis , Magnolia obovata , Magnolia dealbata , and Magnolia grandiflora ) which is distributed throughout the world with main center in east and south‐east Asia . The amount of honokiol in Magnolia officinalis power was found to be of ∼17–19 mg g −1 , while in the bark, phloem, wood, leaf blades, and petioles of fresh Magnolia obovata were of 0.246, 0.155, 0.024, 0.056, and 0.080 mg g −1 , respectively. Data on the pharmacokinetics of honokiol are not yet defined in humans, but are available in a rodent model .…”
Section: Sources and Bioavailabilitymentioning
confidence: 99%
“…Honokiol is a phenylpropanoid molecule isolated and identified in several species belonging to the genus Magnolia (such as Magnolia officinalis , Magnolia obovata , Magnolia dealbata , and Magnolia grandiflora ) which is distributed throughout the world with main center in east and south‐east Asia . The amount of honokiol in Magnolia officinalis power was found to be of ∼17–19 mg g −1 , while in the bark, phloem, wood, leaf blades, and petioles of fresh Magnolia obovata were of 0.246, 0.155, 0.024, 0.056, and 0.080 mg g −1 , respectively. Data on the pharmacokinetics of honokiol are not yet defined in humans, but are available in a rodent model .…”
Section: Sources and Bioavailabilitymentioning
confidence: 99%
“…Due to experimental limitations, we cannot stipulate the concentrations of these pure compounds in the extract. However, in a recent study, Lee et al (2007) did a very similar quantification. They reported that these same gingerols (6-, 8-and 10-gingerol) and 6-shogaol have a concentration of around 2-9 mg g -1 of the raw dried herb, while the amounts were 5-times lower in the dried herb extract.…”
Section: Discussionmentioning
confidence: 78%
“…These are mainly organic and/or aqueous extractions, affecting the recovery of honokiol and magnolol. Sonication, agitation, maceration, or supercritical extraction at variable temperatures for different times (from a few minutes up to 24 h) may be employed to optimize the extraction [18]. This results in widely differing concentrations of magnolol and honokiol in M. officinalis bark crude extracts prepared by different suppliers (▶ Table 3).…”
Section: Magnolol and Honokiol Content In Mbementioning
confidence: 99%